Family support during childhood as a predictor of mate retention and kin care in adults during the COVID-19 pandemic in Brazil: an exploratory study - Tasso, Natália de Araújo Miranda; Castro, Felipe Nalon (Frontiers in Psychology, 2023)
Experiences during development help to explain behavior expression in adulthood. In this study, we explored how unpredictability and harshness experienced during childhood may have impacted the occurrence of reproductive milestones in adulthood and the expression of fundamental motives related to self-protection, disease avoidance, mate seeking, mate retention, and kin care (kids/family) during the pandemic. This was an exploratory study with 438 participants. Through the administration of online questionnaires, participants were assessed and categorized based on their childhood experiences, resulting in three groups: low unpredictability, high unpredictability with family support, and high unpredictability without family support. We found that family support experienced during childhood predicts a slow life history strategy, that is an emphasis on growth and parenting effort at the expense reproduction, being relevant even for participants who faced financial unpredictability. During the pandemic, we also observed that mate retention and kin care (family) motives were predominant among individuals who had greater family support during childhood. Overall, the findings suggest that unpredictability experienced during childhood is crucial for the development of life history strategies and the manifestation of fundamental motives in adulthood.